Pendekatan Holistik dalam Pendidikan: Analisis Multidimensi Biologis, Sosial, Psikologis dan Spriritual - Abdullah Hasyim Zain; Mu’alimin Mu’alimin; Mukaffan Mukaffan (Politeknik Kampar, 2025)
iA iholistic iapproach ito ieducation ihas ibecome ia icrucial iissue iin ithe idevelopment iof icontemporary iscience iand ieducation. iThe irapid idevelopment iof imodern ipsychology idemands ia isynthesis iwithin ian iIslamic iepistemological iframework ito iprovide ia imore icontextual iapproach ito iaddressing iacademic iand ipractical ineeds, iparticularly iin ithe ifields iof ieducation, icounseling, iand icharacter idevelopment. iThis iarticle iaims ito iprovide ibroader iinsights iinto ithe ifactors iinfluencing ichildren's ilearning iand idevelopment. iThis istudy iemployed ia iqualitative iliterature ireview. iArticles iwere icollected ithrough iGoogle iScholar iand iPublish ior iPerish iusing ithe ikeywords i